A Immediate Surgical Obturator and Interim Obturator for Recurrent Nasal Cavity Cancer Patient with Aramany’s Class II: A Case Report - Franciscus Wihan Pradana; Murti Indrastuti; Intan Ruspita; Wardhana, Eugenius Bramianta (Indonesia Prosthodontic Association, 2024)
The maxillary defect can interfere a patient’s speech, masticatory, aesthetic and psychologic. To overcome this problem, an obturator prosthesis is needed. This case report focuses on prosthetic rehabilitation for Aramany’s class II patient. In January 2022, a woman, 46 years old, was diagnosed with recurrent cavum nasi cancer. She got a subtotal maxillectomy at RSUP Dr. Sardjito. After maxillectomy, the patient was assigned a surgical obturator with vacuum formed retainer material to close the palate gap. One month after the operation, the patient came to Oral Clinic RSUP Dr. Sardjito for evaluation. On the intraoral examination, there was a maxillary defect in Aramany’s class II. Resin acrylic obturator with hollow bulb was made as an obturator interim. The obturator insertion showed that the palate gap was tightly closed by the acrylic plate. In this case, the obturator interim successfully helps the patient bring back the function of speech, masticatory, and aesthetics